Pseudospin dynamics in multimode polaritonic Josephson junctions - Pavlovic, G. (2013)
Using Keldysh-Green function formalism we theoretically analyzed the dynamics of multimode exciton-polariton Josephson junctions. We took into account the spinor nature of polaritons and considered in detail the role of coupling of the fundamental modes with excited states. We demonstrate that the coupling to the reservoir results in a change of the oscillation pattern. In particular, it can lead to renormalization of the oscillation frequency, appearance of higher order harmonics, and induce transition between the regimes of free Josephson oscillations and macroscopic quantum self-trapping.